Radiology as a support for examination and treatment in the medical world and its effects: literature review - Hadi Nurvan (Science Midwifery, 2023)
The installation of a radiology unit is part of the service at the Hospital, which provides professional examination services in the form of images to assist doctors in diagnosing and treating patients. This type of radiodiagnostic radiological examination is the use of ionizing radiation with X-rays for diagnostic purposes. Interventional radiography is an examination with X-rays used to guide therapeutic procedures. Occupational safety in radiology has risks, both directly and indirectly, these risks can occur if it fails and other causes beyond human capabilities. As a result of exposure to radiation substances, it has an impact on a person's body in the form of biological radiation effects on humans which can occur in individuals exposed to radiation (somatic effects) or their offspring (hereditary/genetic effects). The physical effects obtained can be immediate or delayed. Somatic effects are divided into non-stochastic (deterministic) effects and stochastic effects, while genetic effects are all stochastic. Considering the large radiation hazard potential in the use of X-rays, safety is an important factor so as to minimize the risks due to work in radiology installations and the impact of radiation on worker radiation. Radiation protection is very important in controlling these adverse effects, in the form of Pb aprons and radiation shields, room facilities that meet the requirements and X-ray equipment have been carried out according to suitability.